THE CONCEPT OF «CHINESE WOMAN» AND RELATED LINGUA-CULTURAL UNITS WHICH EXPRESS THE NAMES OF HANDICRAFTS (Journal of Oriental Studies, 2019)
This article analyzes the concept of «Chinese woman» in the culturological paradigm, and linguocul- tural units related to this concept, which express the names of handicraft products, are also described. In the article examples are given, taken from the work of Cao Xuechin «Dream in the Red Chamber». These fragments of the research show the specificity of the image of the names of women’s handicraft items, which reflect the characteristics of the worldview of Chinese speakersKey words: linguistic cultural units, concept, ethnocultural information, language factor.